Effects of five weeks of resistance training and relatively-dosed creatine monohydrate supplementation on body composition and muscle strength, and whole-body creatine metabolism in resistance-trained males - Andre, T. L.; Gann, J. J.; McKinley-Barnard, S. K.; Willoughby, D. S. (International Journal of Kinesiology & Sports Science, 2016)
Background: Creatine (Cr) supplementation has been established as an ergogenic aid in most individuals during anaerobic exercise. However, discrepancies exist in the data when using absolute dosing. Objective: The effects of five weeks of resistance training with relatively-dosed Cr followed by four weeks of resistance training after ceasing supplementation were determined. Methods: Resistance-trained men, 19 (CR = 9, PL = 10), ingested Cr or placebo for five weeks with resistance training. Participants ingested 0.3 g/kg lean body mass/day for one week, 0.075 g/kg lean body mass/day for four weeks, with a four-week wash out. Five muscle samples, six blood samples, and nine urine samples were collected. Separate two-way ANOVAs for each criterion variable were used employing an alpha level of = 0.05. Results: A group x time interaction for increased total body mass for CR Day 1 and 64 (p = 0.03) and total lean mass for CR Day 1 and 64 (p = 0.01). Group x time interactions occurred for Cr supplementation increasing serum Cr at Day 4, 8, and 22 (p = 0.03), urinary Cr at Day 4 (p = 0.01), and total muscle Cr at Day 8 (p < 0.001), 22 (p = 0.003), and 36 (p < 0.001). No significant differences occurred for serum (p = 0.14) or urine (p = 0.15) creatinine. Conclusion: Elevated levels of urinary Cr demonstrate dosing could be reduced.